Efektivitas Penggunaan Metode Pembelajaran LSQ Terhadap Hasil Belajar Materi Kalimat Efektif Siswa Kelas IV - Cahyani, Aulia Miftahul; Purbasari, Imaniar; Kironoratri, Lintang (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The purpose of this study was to determine the effectiveness of using the Learning Start with a Question method on effective sentences in class IV SDN Widorokandang. This quantitative research was conducted using experimental method. This research was designed using One-group Pretest Posttest quantitative design. This research was conducted in the odd semester of the 2024/2025 academic year. The samples in this study were fourth grade students of SDN Widorokandang consisting of 14 students, consisting of 9 boys and 5 girls. Data were collected through pre-research observations, pre-research teacher and student interviews, pretest and posttest questions to measure students' writing skills and research documentation.This study used the Paired Sample T-Test test to determine whether there was an influence before and after being given treatment using the Learning Start with a Question method. The results of the Paired Sample T-Test analysis show that the significance level with sig. (2-tailed) of 0.000 <0.05 means that there is an average difference between the pretest and posttest. It can be concluded that students are able to show effective sentences, complete words, complete punctuation, compose words and write stories well after the application of the Learning Start with a Question learning method on effective sentence material for grade IV students of SDN Widorokandang.